The paradoxical success of corrupt politicians: evidence from a field experiment - Queirós, Sara Maria Silvério Marques Amorim (2018)
This paper contributes to the literature on the explanations for the often observed phenomenon of the electoral success of corrupt politicians. It focuses on the particular case of the Portuguese municipality of Oeiras, where Isaltino Morais was elected as mayor after being convicted for corruption-related crimes. We collected data on 557 residents of the municipality. Data were collected four weeks after the October 2017 election. We find no evidence for the ignorant voter explanation but strong support for the implicit trading theory.